A W-Band Radiometer with the Offset Parabolic Antenna for Radiometric Measurements - Li Wu; Shu-sheng Peng; Jian-zhong Xu; Ze-long Xiao (International Journal of Antennas and Propagation)
This paper deals with the development of a W-band noise-adding radiometer which combines the millimeter-wave (MMW) radiometric measurements with a high-resolution imager. The offset parabolic antenna is presented to achieve an accurate measurement and a high resolution. To reduce the cross-polarization level of the antenna, a multimode feed horn with a multistep structure is proposed to match the focal region fields of the reflector. It has advantages over the corrugated horns in lower mass and easier manufacturing. In addition, due to an unavoidable settling time for the noise-adding radiometer output signal passing through the low-pass filter, a theoretical criterion for the optimum duty cycle determination to reject extraneous contributions from the transient is proposed in this paper. The appropriate duty cycle threshold is 0.33 for the developed W-band radiometer. Also, a geometric correction method is presented to correct the obtained passive image suffering from a distortion for a better image interpretation. Preliminary experimental results are given to illustrate and verify the presented techniques.